Characterization of Cellulose Acetate Membrane at Different Thicknesses on Sucrose Concentration by Forward Osmosis - Aida I. Mohamad Idris; Siti Mazlina Mustapa Kamal; Alifdalino Sulaiman; Rozita Omar; Munira Mohammad (Department of Chemical Engineering, Universitas Gadjah Mada, 2022)
Forward osmosis (FO) requires a specific membrane structure for applications like juice concentration. The phase inversion method was used to make cellulose acetate (CA) FO membranes. The solvents used were acetone and 1,4-dioxane. Additives included polyvinylpyrrolidone (PVP), methanol, and maleic acid were used in the preparation of CA membrane, which make it easier to improve a FO membrane's permeability. The performance of fabricated FO membrane and their morphology were evaluaed with different casting thicknesses of 150, 200, and 250 µm. Experiment works begins with an hour of membrane flux testing, deionized water was used as feed solution and 1 M NaCl as draw solution. The membrane was then used to concentrate 0.5 M sucrose with NaCl for 240 minutes (2 M). Contact angle, porosity, and scanning electron miscroscopy (SEM) were used to characterize membrane properties and morphology. High water flux (2.25 L/m2hr) and high porosity (75.86%) were found at 200 µm casting thickness. Water permeability of sucrose concentration at 200 µm casting thickness had the highest flux (2.39 L/m2hr). The results also show that flux values vary with membrane thickness. All membranes were hydrophilic with contact angles below 90°. A 200 µm casting thickness produces a membrane with smooth and evenly distributed pores, according to morphology analysis. Structural parameter (S) values had a proportional relationship with the FO membrane thickness, which thinner membrane potentially reduces the internal concentration polarization (ICP).